PERBEDAAN LATIHAN LARI CEPAT DITAMBAH LATIHAN DOUBLE LEG BOUND DAN ALTERNATE LEG BOUND TERHADAP KECEPATAN LARI 50 METER PADA PELARI PEMULA (Department of Sports Science, Faculty of Sports Science, Universitas Negeri Semarang, 2014)
Tujuan: 1). Untuk mengetahui pengaruh latihan double leg bound dan alternate leg bound terhadap hasil lari 50 meter pada pelari pemula 2). Untuk mengetahui pebedaan latihan double leg bound dan alternate leg bound terhadap hasil lari 50 meter pada pelari pemula. Metode: Populasi penelitian ini adalah siswa kelas XI IPA Putra SMAN 2 Sukorejo yang berjumlah 14 siswa. Sampel dalam penelitian berjumlah 14 siswa. Pengambilan sampel menggunakan teknik total sampling. Variabel penelitian ini yaitu latihan Double leg bound dan Alternate Leg Bound sebagai variabel bebas serta hasil lari 50 meter sebagai variabel terikat. Metode penelitian menggunakan eksperimen. Metode analisis data yang digunakan adalah uji t-test . Simpulan: hasil penelitian ini adalah 1) Latihan lari cepat ditambah latihan double leg bound mempunyai pengaruh terhadap peningkatan waktu tempuh lari 50 meter pada pelari pemula; 2) Latihan alternate leg bound mempunyai pengaruh terhadap peningkatan waktu tempuh Lari 50 meter pada pelari pemula. 3) Latihan lari cepat ditambah latihan alternate leg bound lebih baik daripada latihan lari cepat ditambah latihan double leg bound terhadap kecepatan lari 50 meter pada siswa kelas XI IPA Putra SMAN 2 Sukorejo. Saran: yang dikemukakan dalam penelitian ini adalah : 1) Diharapkan pada siswa dan guru pada umumnya dalam membina kemampuan khususnya untuk meningkatkan daya ledak otot tungkai bisa menggunakan metode latihan plaiometrik yang salah satunya yaitu latihan Alternate leg bound. 2) Kepada peneliti lain, hasil penelitian ini dapat digunakan sebagai pembanding untuk penelitian sejenis lainnya.The problem in this research is : 1) Is there influence exercise double leg bound to result run 50 meters at novice runners? 2). Is there influence exercise alternate leg bound to result run 50 meters at novice runners? 3). What the difference was exercise double leg bound and alternate leg bound to result run 50 meters at novice runners? The purpose of this research is: 1).To know influence exercise double leg bound and alternate leg bound to result run 50 meters at novice runners, 2).To know different exercise double leg bound and alternate leg bound to result run 50 meters at novice runners. Population this research is graders IPA XI Class SMAN 2 Sukorejo Student’s which totaled 14 students. Samples in research totaled 14 students. The sample used technique total sampling. Variable research is exercise double leg bound and alternate leg bound as variable free and the result of run 50 meter as variable bound. Method research use experiments. A method of data analyzed used is t-test Conclusion this research result is 1) an exercise run away quickly plus exercise double leg bound impact on the results of the travel time run 50 meters at novice runners; 2 ) an exercise alternate leg bound impact on the results of the travel time run 50 meters at novice runners. 3 ) there are differences that result run 50 meters at the time of posttest in the first experiment and second experiment. Exercise run away quickly plus the exercise of alternate leg bound better than exercise run away quickly plus exercise double leg bound to the speed run 50 meters at novice runners. Advice was stated in this research is: 1) is expected in student and teacher in general within fostering ability esp. to increase explosive power limb muscles can use methods exercise Pliometrik that one of them is exercise alternate leg bound. 2) to the other researcher, this research result can be used by contrast for research other similar.